ASSESSMENT OF PROFESSIONAL DEVELOPMENT BY TEACHERS AND ADMINISTRATORS: AN EXAMINATION OF THE LITERATURE IN THE CONTEXT OF ONE CASE STUDY - Hinds, Marjorie; Berger, Marie Josée (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
<!--StartFragment--> ABSTRACT. The focus of this article is teacher professional development. The article examines literature related to teacher professional development and methods of measuring its impact. In order to ground the discussion, the article focuses on a case study that captures the perspectives of Ontario secondary school teachers and their administrators as they implement a literacy program targeted at improving student achievement. ÉVALUATION DU DÉVELOPPEMENT PROFESSIONNEL PAR LES ENSEIGNANTS ET LES ADMINISTRATEURS: UNE ANALYSE DE LA LITTÉRATURE DANS LE CONTEXTE D’UNE ÉTUDE DE CAS RÉSUMÉ. Les stratégies relatives à la réussite des élèves sont souvent assujetties à la compréhension des liens entre le perfectionnement professionnel des enseignants et le développement de la littératie des élèves. En plus d’examiner la littérature portant sur le perfectionnement professionnel et les mesures relatives à son impact, cet article présente une étude de cas qui relate les représentations des enseignants des écoles secondaires de l’Ontario et des administrateurs scolaires durant le processus de mise en œuvre d’un programme de littératie visant l’amélioration du rendement des élèves. <!--EndFragment-->